Pomegranate juice protects kidneys from Cisplatin-induced nephrotoxicity - Aljebori, Hussain A.; Abady, Ali H.; Jaffar Alalsaidissa, Jaffar N. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Cisplatin is a potent anti-cancer agent used successfully in treatment of cancers of solid organs, but it has a high rate of nephrotoxicity. Objective: The present study was designed to study Cisplatin-induced nephrotoxicity and the nephroprotective property of pomegranate juice. Materials and Methods: The experiment was performed on 36 Iraqi white male domestic rabbits. Rabbits were divided into three groups; control group (received neither pomegranate juice, no Cisplatin), Cisplatin group (received Cisplatin only), and pomegranate group (received pomegranate juice and Cisplatin). Results: Cisplatin group showed marked reduction of renal function manifested by high levels of blood urea, serum creatinine, and low level of serum albumin.Raised levels of oxidative stress markers and severe renal parenchymal damage by histopathology.While, pomegranate group showed almost normal renal function tests and normal levels of oxidative stress markers, and normal renal parenchymal histopathology. Conclusion: Cisplatin in a highly nephrotoxic drug, and Pomegranate juice has a nephroprotective activity against Cisplatin-induced nephrotoxicity.